A Project Feasibility Study on DOLCE TOMATO POWDER - Garcia, Paolo (College of Engineering, 2002)
For the past fifty to sixty years, tomato powder has been existing in other countries but has not yet penetrated the Philippine market. Few people here in the Philippines are aware of it and the advantages of using it. The tomato powder is basically fresh tomato that is dried/dehydrated and then pound for it to be in the powdered form. Powdered tomato has several advantages over the conventional tomato sauce and paste. First, tomato powder has a longer shelf life. Tomato powder has a minimum shelf life of one year. Second is that it is cheaper than the conventional tomato sauce and paste because it undergoes a simpler process. In order to know if the production and marketing of the tomato powder will be profitable here in the Philippines, a feasibility study has to be undertaken. The feasibility has several parts, but for this study, it will only include the market, technical, financial and socio-economic profitability of the project. The first study to be done is the market study. Based on the survey made from the market study, it was found about that 29% of the consumers are willing to try DOLCE Tomato Powder. The main reasons for this is that the price of the Dolce tomato powder is lower than its competitors, it has a longer shelf life, and that the user has the option of varying the reconstitution of the tomato paste or sauce depending on their taste preference. This also shows the tendency of Filipino consumers to try a new product especially when it's much cheaper. Also, based from the survey, it is found out that both household and commercial establishments are willing to try the Dolce tomato powder. After establishing that there is a market for the Dolce tomato powder, the technical study follows. From the technical study it is found out the production of Tomato Powder is technically feasible. This is so because of the following reasons. Firstly, it is found out that there is an existing process as well as the available technology in producing tomato powder. From the technical study it is determined that the tomato powder will be produced in a semi automated process mainly because of the large volume of production. In this process fresh tomato will undergo washing, sorting, blanching, cutting, straining, drying and then packaging. Secondly, the required raw material can be supplied by the selected supplier through contract growing so that it can be assured that there is a constant supply of fresh tomatoes. Thirdly, it is also found out there are available sources of the needed equipment and tooling for the process, however, most of the suppliers are foreign. For the cost of the project, the total initial investment of the company is P22,926,663.00 while the operational expenditure of the company for the first year of operation is estimated to be P39,670,673.73. Adding these two costs will sum up to the total estimated project cost of P62,597,336.73. After establishing that from the financial study, the computed total project cost was found to be P33,998,901.70. This value is different form project cost from technical study because the working capital or operation cost is only good for three months. Unlike in the operation cost of the technical study which is good for one year. The reason for this is that after three months, the project is expected to earn profit and this profit will be used to finance the operating expenses of the project. Also from the financial study, it is found out that the total project cost of P36,998,901.70 is fundable based on the evaluation of the different financing institutions. The Countrywide Industrialization Fund, which has the lowest interest and good repayment terms, is chosen to be the financier of the project. Also, income statement and the balance sheet are projected in the financial study to show the financial standing of the project. Several tests are also conducted to find out if the project is profitable. Some of it is the debt-to-net worth ratio, which indicates a lower debt pressure and greater protection from creditors. Another test is the return on net operating profit indicates a greater profitability of making appreciable addition to the owner's capital after payment of dividends and taxes. Based on these tests, the project is proven to be a profitable investment. Breakeven analysis is also performed. From the analysis it is found out that the initial level of production was found out to be above the breakeven level of production for both 500-gram and 30-gram pack. Also, the estimated price was above the breakeven price for both the 500-gram and the 30-gram pack. Also included in the financial study is the Net present Value Analysis and the Internal Rate of Return. The project has a net present value of P62,613,851.09 and an internal rate of return of 169%. And lastly for the social-profitability study, the project is said to be feasible because of the following reasons: Firstly, the project will generate employment. Secondly, the project will also generate taxes for the government. Thirdly, the province of Ilocos Sur will benefit from the project because of the community tax that will be getting from the project. Thirdly, instead of using imported tomatoes, the project will use local tomatoes from Ilocos Sur. This will benefit the farmers of that region. And lastly, the market can have a cheaper and better substitute to the existing tomato paste and sauces. And the consumer can be proud of it because it is a Filipino made product. Having proven that the project is feasible in the market study, technical study, financial study, and socio economic study, the project of stating the production and marketing of the Dolce tomato powder can truly be said a feasible project.